2021
DOI: 10.3389/fpubh.2021.726727
|View full text |Cite
|
Sign up to set email alerts
|

Struggling With Business Corporate Cynical Impression? Powerful Methods of CSR to Enhance Corporate Image and Consumer Purchase Intention

Abstract: This study focuses on the perception of Chinese students about the image of the company and their purchase intention if the organization has a business cynical impression in the minds of its targeted customers. The study proposed three different types of corporate social responsibility (CSR) to cope up with the organizational cynical impression. These types are Economic and Legal CSR, Philanthropic CSR, and Ethical CSR. The main objective of this study is to determine which CSR type is better to reduce the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…The highest value for the composite reliability is 0.938 and the lowest value for the composite reliability is 0.786, making all the variables reliable. All the values in this study were found reliable according to Avotra et al (2021b) . Furthermore, the factor loading of the items obtained in this study was all above 0.6 and the average variance extracted (AVE) also met the cut-off value mentioned in literature, i.e., 0.5 ( Galaz et al, 2021 ).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The highest value for the composite reliability is 0.938 and the lowest value for the composite reliability is 0.786, making all the variables reliable. All the values in this study were found reliable according to Avotra et al (2021b) . Furthermore, the factor loading of the items obtained in this study was all above 0.6 and the average variance extracted (AVE) also met the cut-off value mentioned in literature, i.e., 0.5 ( Galaz et al, 2021 ).…”
Section: Discussionsupporting
confidence: 65%
“…There were two independent variables, i.e., affordable energy resources (3-item scale was adapted from Moşteanu et al, 2020 ) and technological use (5-item scale was adapted from Ciocoiu, 2011 ); one dependent variable sustainable digital economy (7-item scale); one moderator low operations cost (3-item scale was adapted from Moşteanu et al, 2020 ); and a mediating variable, i.e., sustainable development (4-item scale was adapted from Dantas et al, 2021 ). The results from the measurement model showed the alpha and composite reliabilities in the acceptable range, i.e., >0.70 ( Avotra et al, 2021b ). The measurement model can be seen in Figure 2 .…”
Section: Methodsmentioning
confidence: 97%
“…This study follows a positivist approach. Avotra et al (2021b) have defined the positivist approach as research that examines the causes of a variable that affect another variable. In this deductive study, the hypothesisbased theory has been proposed based on the literature review done that is either validated or refused with the help of different analysis techniques.…”
Section: Methodsmentioning
confidence: 99%
“…The digital economy is characterized by integrating technology and the capacity to bridge the gap across digital, physical, and biological systems. It is commonly referred to as a digital information-based economy ( Avotra et al, 2021a , b ).…”
Section: Literature Reviewmentioning
confidence: 99%